Uniaxial Tension Behavior of FeNiCrCoAl and FeNiCrCoTi Complex Concentrated Alloys: A Molecular Dynamics Approach (University of Thi-Qar Journal for Engineering Sciences, 2024)
Complex concentrated alloys have been thoroughly examined for their excellent mechanical properties. In the present study, phase transitions and mechanisms of dislocation for FeNiCrCoAl and FeNiCrCoTi complex concentrated alloys were examined using classical molecular dynamics simulations under uniaxial tension. The (LAMMPS) code was used to simulate CCAs systems by using EAM potentials. The effect of strain rate change has been taken into account. The results show that at the early plastic stage, the main deformation behavior is the transition from FCC to HCP phase. Moreover, tensile characteristics are negatively affected by strain rate rise. At strain rate value of , for FeNiCrCoAl, elastic modulus and density are computed to be and . Whereas, for FeNiCrCoTi, elastic modulus and density are calculated to be and . It can be noticed that elasticity modulus of FeNiCrCoAl is two times greater than that of FeNiCrCoTi. In contrast, young modulus of complex concentrated alloys decreases succinctly when the strain rate increases to a value of . Under tensile deformation, the movement direction and impact on mechanical properties of the prevalent 1/6 <112> Shockley partial dislocations are analyzed.